Effect of Foreign Investmentiand Domestic Investment to Regional Income in Sumatra Provincewest - Syaputra, Fery Yunas; Martilova, Novera (Kompartemen: Kumpulan Orientasi Pasar Konsumen, 2023)
Regional income seen from GRDP canadescribe the economicsbgrowthnof avregions. thebhigh levelbof economicsagrowth as indicatedbby thevhigh GRDPbvalue indicatesbthat thenregion isbexperiencing progressbin thexeconomy.aSources of receipt of Regional Income in West Sumatra Province are influencedcby Investmentafactors, bothafrom PMAaand PMDN on Regional Income.athexproblemninnthisvstudybis howbthe influencenof FDI and PMDN on regional income in West Sumatra Province. thenpurpose ofsthis researchbis to findcout hownmuch influencebFDI and PMDN haveton Regional Incomebin WestbSumatra Province.athis research isva quantitativearesearch withnsecondary databin the 2000-2021 observationsbperiod. Databcollection inbthisnstudy used thendocumentation method for the realization of FDI and PMDN, the amount of Gross Regional Domestic Product obtained from BPS,athe collected data was analyzed usingbmultiple linear regression analysis. Overallathe results of multiple linearnregressionaanalysis and hypothesis testing can be concluded that partially (T test) Foreign Investment (X1) has a significantaeffect on Regional Income with a significant value of 0.049 <0.05 and with at count value of 2.101 > t table 2.09302 . While Domestic Investment (X2) with a significant value of 0.000 <0.05 and a t-count value of 6.195 > t-table 2.09302 so from these results it can be concluded that Domestic Investment has a significant effect on Regional Income. And simultaneously (Test F) shows a significant result of 0.000 <0.05, which means that the FDI and PMDN variables simultaneously influence Regional Income. With a Determinant Coefficient (R Square) of 0.745, which meansbthat the influence caused by theathe independent variables in this case explaining Regional Income is 74.5%.